2021
DOI: 10.24252/minds.v8i1.19316
|View full text |Cite
|
Sign up to set email alerts
|

Human Capital Development of Research Staff through Self-Leadership, Teamwork Management, and Culture Diversity

Abstract: Research related to the development of human capital based on cultural diversity is still minimal, so this study aims to find a human capital development model based on cultural diversity, self-leadership, and team management. The research instruments used questionnaires with samples of 146 respondents; the data was processed using SEM. The results showed that human capital performance could improve if supported by solid self-leadership despite cultural diversity. However, the research staff has not been able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Manifestations of cultural diversity tend to affect thinking and habits, so it is often referred to as cultural intelligence (Zoogah, 2016). The cultural diversity that emphasizes diversity will influence human practices, attitudes, and mindsets (Jusriadi et al, 2021). The consistency of cultural diversity will be tested when specific individuals or groups cannot understand well so that this condition is feared to trigger conflict (Mickson et al, 2020).…”
Section: Culture Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…Manifestations of cultural diversity tend to affect thinking and habits, so it is often referred to as cultural intelligence (Zoogah, 2016). The cultural diversity that emphasizes diversity will influence human practices, attitudes, and mindsets (Jusriadi et al, 2021). The consistency of cultural diversity will be tested when specific individuals or groups cannot understand well so that this condition is feared to trigger conflict (Mickson et al, 2020).…”
Section: Culture Diversitymentioning
confidence: 99%
“…The consistency of cultural diversity will be tested when specific individuals or groups cannot understand well so that this condition is feared to trigger conflict (Mickson et al, 2020). However, if certain individuals or groups can properly manage cultural diversity, it will give birth to job satisfaction and competitive advantage (Jusriadi et al, 2021). Several researchers have researched cultural diversity.…”
Section: Culture Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, study results (Javadi et al, 2013), focusing on the relationship between selfleadership strategies and job satisfaction, concluded that self-leadership strategies significantly affect job satisfaction in Iran. Furthermore, research (Jusriadi et al, 2021), focusing on human resource development research staff through self-leadership, concluded that human capital performance can improve if supported by solid self-leadership. Therefore, based on several previous research results, this study is carried out in developing hypotheses: H1: Self-leadership affects work satisfaction H5: Self-leadership affects human capital performance…”
Section: Literature Review Self-leadershipmentioning
confidence: 99%
“…Performance in the perspective of human resource development (HR), both in task performance and contextual performance capital, is not only measured by the availability of tangible assets in the form of physical capital and financial capital (Jusriadi et al, 2021). The achievement of work results in quality and quantity achieved by an employee within a specific time is the essential part of the organization's goals (Na-Nan & Saribut, 2020).…”
Section: Human Capital Performancementioning
confidence: 99%